Metabolic syndrome and prostate cancer in Afro‐Caribbean men. Issue 3 (14th December 2021) - Lefebvre, Florian; Blanchet‐Deverly, Anne; Michineau, Leah; Blanchet, Pascal; Multigner, Luc; Brureau, Laurent
Abstract: Introduction and Objectives: Metabolic syndrome (MetS) is a group of risk factors that increases the likelihood of developing cardiovascular diseases. Although suggested, the relationship between MetS and prostate cancer (PCa) is still inconclusive. Very few studies have addressed this question in populations of African descent, which are disproportionately affected by PCa. This study aimed to assess the prevalence of MetS among incident cases of Afro‐Caribbean PCa and estimate its association with adverse clinicopathological features and the risk of biochemical recurrence (BCR) after radical prostatectomy (RP). Materials and Methods: We included 285 consecutive patients with incident cases of PCa attending the University Hospital of Guadeloupe (French West Indies). MetS was evaluated at the time of diagnosis by collecting information on blood pressure, glycaemic status, triglyceride and high‐density lipoprotein cholesterol levels, and obesity through various surrogates, including two waist circumference indicators (≤94 cm, ≥102 cm), the waist‐to‐hip ratio (≥0.95), and body mass index (BMI; ≥30 kg/m 2 ). We followed 245 patients who underwent RP as primary treatment of localized PCa. Results: The prevalence of MetS varied greatly, from 31.6% to 16.4%, when a waist circumference ≥94 cm or BMI were used as obesity surrogates, respectively. No significant associations were found between MetS, regardless of the obesity criteria employed, and the risk of adverse pathological features or BCR. Conclusions: The high variability in MetS resulting from the diversity of obesity criteria used may explain the discordant associations reported in the literature. Further studies using strict and uniform criteria to define MetS on homogeneous ethnic groups are encouraged to clarify the association, if any, between MetS and PCa outcomes.